Menghindari Plagiarisme dengan Pemahaman Etika Mengutip dari Sudut Pandang Information Technology ethic, Regulation and Cyber Law - Aji, Ranggi Praharaningtyas; Albana, Ilham; Akmal, Rafii Nur; Aulia Difa, El Syafangatun; Waluyo, Retno (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The creation of scientific works is inseparable from the activities of searching, processing, and citing existing information. Mistakes in obtaining information or citing from literary sources will result in significant problems. Accusations of plagiarism and even legal action can be taken against individuals who produce scientific articles with the label of plagiarism. The writing methods or the use of citation management tools are still not optimal in reducing the level of plagiarism. The knowledge and awareness of writers about the importance of preserving and respecting the works of others become crucial to understand. Training becomes an effective solution to enhance the knowledge and awareness of writers about the importance of preserving and respecting the works of others, which are intellectual properties. The method used in the training involved lectures and discussions, integrating the material into the Information Technology Ethics, Regulation, and Cyber Law course. After the community service activities were conducted, it can be concluded that 79% of students felt an increase in knowledge regarding the dangers and importance of avoiding plagiarism, and the community service activities were effective in providing education and understanding to the students.